IBN TAYMIYYAH’S PHILOSOPHICAL CRITIQUE TO IBN ‘ARABĪ’S WAḤDAT AL-WUJŪD THOUGHT - Hakim, Lukmanul; Ahmad, Ahmad; Tri Hadi, Rahmad (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
This research aims to describe and analyze Ibn Taymiyyah’s philosophical-constructive critique of Ibn ‘Arabī’s waḥdat al-wujūd thought. The method used in this research is descriptive-analytical. The primary data used in this research are the works of Ibn Taymiyyah and Ibn ‘Arabī. Meanwhile, secondary data in this research are books, journal articles, and other websites that discuss the thoughts of Ibn Taymiyyah and Ibn ‘Arabī. The research results show that Ibn Taymiyyah rejected thinking of waḥdat al-wujūd, because of his understanding of the doctrine of waḥdat al-wujūd This is different from the understanding of Ibn ‘Arabī and his followers. According to Ibn Taymiyyah, waḥdat al-wujūd is the equating of God with nature. In modern terms synonymous with pantheism. Ibn Taymiyyah said those who adhere to waḥdat al-wujūd say that existence is one, and wajib al-wujūd what God has is the same as possible waḥdat al-wujūd that a creature has. Ibn Taymiyyah’s criticism emerged because he only saw aspects of tashabbuh (equation of God with his creatures) from understanding waḥdat al-wujūd, and did not see aspects of tanzīh (purification of God from the likeness of his creatures) from the same understanding. These two aspects are combined into one in the teachings of Ibn ‘Arabī. Even according to Ibn Taymiyyah, the understanding that considers God’s existence to be united with the existence of His creatures is a form of disbelief for God, a form of disbelief and shirk in Him.